Intelectualidades negras e mestrado acadêmico em ensino: contribuições para discussões decoloniais - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The general objective of this dissertation was to investigate how the intellectualities of black people, who have the Academic Master's in Teaching (MAE) at the Federal University of Pampa (UNIPAMPA) as a common point in their trajectories, impact and are impacted by the program. To this end, the following specific objectives were drawn up: to identify the profiles and pluralities of black students on the PPGE; to learn about the resistance present in the multiple professional and intellectual performances of these subjects; and finally, to present reflections based on the author's experiences during the program. In this way, the subjects who participated in the construction of the research are black women students or graduates of the Postgraduate Program in Teaching at UNIPAMPA Bagé campus. The theoretical framework is anchored in decolonial studies and in the knowledge built up in the black and transfeminist movements. The tools used to carry out the research were autoethnography and focus groups, thought of here not only as data production, but also as crossroads that enabled confluences and (trans)formations in intersubjective exchanges. The analysis was built on emerging themes from the focus groups, which were then reorganized and related to the references that underpinned the study. The research took on the character of a tool for evaluating the program on the part of the participants and, in this way, it was necessary to access official documents, which are listed in the analysis in order to understand how affirmative action has been constructed in the PPGE. It is clear from the intersectional examination that the majority of subjects who occupy spaces in the PPGE are white cis women without disabilities, and in terms of access through affirmative action, the majority are black cis women without disabilities. In addition, the research demonstrates the need for collective organization based on self-identification as a black person in order to bring about changes in this context. Thus, it is possible to infer that research groups and qualification and dissertation boards have been strategically designed as spaces to expand theoretical dialogues and methodological possibilities. Also in its results, the work points out that black intellectuals, based on the dialogues that emerged in the focus groups, constructed discussions and reflections that led to a collective refinement of criticality involving debates on affirmative action and the organization of the program, as well as analyses of the perceptions of the subjects in the power-knowledge relations that are crossed by the markers of social differentiation.
Black intellectualities and the academic master's in teaching: contributions to decolonial discussions
Keywords: Ensino; Intelectualidades negras; Autoetnografia; Decolonialidade; Cisgeneridade; Teaching; Black intellectuals; Autoethnography; Decoloniality; Cisgenerity; CIENCIAS HUMANAS